2004
DOI: 10.1029/2004gc000738
|View full text |Cite
|
Sign up to set email alerts
|

Focused magmatism versus amagmatic spreading along the ultra‐slow spreading Southwest Indian Ridge: Evidence from TOBI side scan sonar imagery

Abstract: [1] The analysis of the Towed Ocean Bottom Instrument (TOBI) side scan sonar images along the Southwest Indian Ridge between 63°40 0 E and 65°40 0 E reveals strong focusing of magmatic activity and long amagmatic accretionary ridge segments. Fresh-looking volcanic terrains are observed at distinct locations along the axis separated by highly tectonized and sedimented terrains of an alongaxis extent as much as 82 km. The largest tectonized section corresponds to a dramatically thin crust area with moderate magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 49 publications
2
61
0
Order By: Relevance
“…3b). Considering the idealized two-dimensional triangular melting regime beneath an ocean ridge, a good deal of mantle rock is removed from the melting column as the mantle rises up to the base of the crust; consistent with the evidence for focused flow of melt in the shallow mantle beneath ocean ridges ( [31][32][33] ). Thus, models for MORB genesis must take this into consideration.…”
Section: Thermodynamic Modeling Of Morb and Peridotite Genesissupporting
confidence: 68%
“…3b). Considering the idealized two-dimensional triangular melting regime beneath an ocean ridge, a good deal of mantle rock is removed from the melting column as the mantle rises up to the base of the crust; consistent with the evidence for focused flow of melt in the shallow mantle beneath ocean ridges ( [31][32][33] ). Thus, models for MORB genesis must take this into consideration.…”
Section: Thermodynamic Modeling Of Morb and Peridotite Genesissupporting
confidence: 68%
“…The rocks exposed on the seafloor are mainly basalts, with some gabbros, pyroxenites and serpentinized peridotites [12]. Sauter et al [18,19] and Cannat et al [20] discussed the melt supply processes based on gravitational, magnetic and petrological data. They found that at the ultraslow-spreading ridges, the melt may migrate horizontally along the axis and mantle upwelling may be focus at some specific sections [18][19][20].…”
Section: Geological Settingmentioning
confidence: 99%
“…Sauter et al [18,19] and Cannat et al [20] discussed the melt supply processes based on gravitational, magnetic and petrological data. They found that at the ultraslow-spreading ridges, the melt may migrate horizontally along the axis and mantle upwelling may be focus at some specific sections [18][19][20]. Moreover, the ridge spreading and hydrothermal activities may interact with hot spots such as the Marion, Bouvet, Del Cano and Crozet plateau [21,22].…”
Section: Geological Settingmentioning
confidence: 99%
“…In this context, the pronounced along-axis topographic and MBA gradients associated with the volcanoes may define the boundaries of more magmatic second-order spreading segments. Alternatively, several authors have proposed that melt produced in the mantle beneath the adjacent nearly amagmatic domains could be focused for over tens of kilometres toward the volcanoes (Cannat et al 1999Okino et al 2002;Sauter et al 2004;Standish et al 2008;Cochran 2008). In this case, the second-order segments in these ultraslow ridge regions would also include part of the amagmatic domains adjacent to axial volcanos.…”
mentioning
confidence: 99%